Strength characteristics of sealer devices at design stage; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Butov V. G. Vladimir Grigorievich; Golubeva K. A.; Nikulchikov V. K. Viktor Kensorinovich; Yashchuk A. A. (Latest Technology in Oil-and-Gas Pipelines and Petroleum Storage, 2016)
Title screen